(untitled) (Research, Society and Development, 2021)
Recent studies have evaluated the effect of the use of biofilms as coating on fruits and vegetables, intending to reduce respiratory metabolism and sweating. Therefore, the objective was to evaluate the postharvest quality of umbu tree fruits submitted to cassava starch and PVC coating. The fruits were harvested in the city of Campo Redondo-RN and transported to IFRN, Currais Novos campus. The fruits were sanitized and submitted after drying coatings with 3% cassava starch and PVC film. Then the fruits were stored at 24°C and relative humidity of 44%. Mass loss, external appearance, peel color, longitudinal and transverse diameter, pH, titratable acidity, soluble solids and ratio were analyzed. It was verified that the application of PVC coating on fruits showed higher effectiveness compared to starch coating providing better fruit appearance, lower water loss and lower soluble solids content at the end of storage. The use of the coating with cassava starch at 3% was not efficient in reducing the loss of mass, caused a greater reduction in diameter and delayed the yellowing of the fruits. The shelf life of fruits covered with cassava starch at 3% was 3 days, while the fruits covered with PVC and the control fruits were 4 days.